ANTIMICROBIAL POTENTIAL OF COCONUT OIL IN BACTERIA CULTURED FROM THE ORAL ENVIRONMENT - Gabriel Brito Brandão, Gerson; Pedro Costa De Oliveira, Gledyson; Cosmo Melo, Hadiellson; Alexandre Santos Silva, Jonas; Henrique Fernandes Macedo, José (Journal of Interdisciplinary Debates, 2024)
The study addressed the antimicrobial potential of coconut oil, both extra virgin and homemade, against oral bacteria. For this evaluation, chlorhexidine was used as a comparison standard. The tests were conducted in five culture media, one for chlorhexidine, another for extra virgin coconut oil, and a third for homemade coconut oil. The results revealed that extra virgin coconut oil exhibited partial inhibition of bacterial growth, being effective only against certain strains, while homemade coconut oil showed no considerable effectiveness in any test. On the other hand, chlorhexidine displayed the expected and excellent antimicrobial action. These results highlight the need for further studies on extra virgin coconut oil, especially to better understand the bacteria it inhibits, in order to promote a more effective use of this compound.